The rhetorical move–step structure of highly cited articles in linguistics - Harfiani, Malihah; Kurniawan, Eri; Dallyono, Ruswan (UNIB Press, 2025)
Writing scientific articles is a major concern for novice writers, and studying rhetorical moves is an appropriate approach to address this issue. This study aims to analyze rhetorical moves in 30 highly cited international journal articles in the field of linguistics and to examine the pattern arrangements in the Introduction, Methods, and Results-Discussion-Conclusion (RDC) sections. Using a qualitative content analysis combined with frequency analysis across various frameworks, the study is grounded in Swales’ (1990) theory, which conceptualizes rhetorical moves as functional components in academic writing. The findings reveal that the most frequently occurring rhetorical moves consist of eight: three in the Introduction, two in the Methods, and three in the RDC section. Each move comprises specific steps: the Introduction includes three steps, the Methods section also includes three steps, and the RDC section consists of eight detailed steps. The pattern arrangements identified are [M1 M2 M3] and [M1 M3] in the Introduction, [M1 M2 M1 M2] in the Methods, and [M3 M4 M3 M4 M5] in the RDC section. These findings highlight the importance of move-pattern awareness in academic writing and offer practical guidance for novice writers seeking to emulate effective rhetorical structures in scholarly discourse